2015
DOI: 10.1007/s12595-015-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Clove Oil Efficacy on the Red Spider Mite, Oligonychus coffeae Nietner (Acari: Tetranychidae) Infesting Tea Plants

Abstract: The tea red spider mite, Oligonychus coffeae Nietner (Tetranychidae), is an economically important pest of agricultural and ornamental crops and considered one of the major pests of tea plants in North-east India. In view of increasing resistance recorded in insect and mite pests against pesticides, a study was conducted to determine the acaricidal, antiovipositional, repellent and ovicidal activities of clove oil (an essential oil from the clove plant, Syzygium aromaticum L. Merr. & Perry: Myrtaceae) against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In another study,Lee et al (1997) reported that carvacrol, thymol, and eugenol from monoterpenoids exhibited 100% mortality at 10.000 ppm after 24 hours in T. urticae. Similar to our study, S. aromaticum (1.5% concentration) showed a mortality rate of 53.33, 63.33, 73.33 and 98.54% in Oligonychus coffeae Nietner (Acari: Tetranychidae) after 24, 48, 72 and 120 hours, respectively(Barua et al 2015).…”
supporting
confidence: 90%
“…In another study,Lee et al (1997) reported that carvacrol, thymol, and eugenol from monoterpenoids exhibited 100% mortality at 10.000 ppm after 24 hours in T. urticae. Similar to our study, S. aromaticum (1.5% concentration) showed a mortality rate of 53.33, 63.33, 73.33 and 98.54% in Oligonychus coffeae Nietner (Acari: Tetranychidae) after 24, 48, 72 and 120 hours, respectively(Barua et al 2015).…”
supporting
confidence: 90%
“…As an alternative to synthetic chemicals, plant-derived essential oils (EOs) are increasingly being used as biorational products in agriculture. Various scholars [30,[106][107][108][109] have argued that essential oils show antimicrobial, acaricidal, insecticidal, molluscicidal and nematicidal properties while demonstrating little or no toxicity to humans and the surrounding environment. The molluscicidal properties of essential oils have been mostly confirmed against terrestrial molluscs [110].…”
Section: Natural Products As Biorational Control Agents Of Slugsmentioning
confidence: 99%
“…Essential oils are promising because they can kill slugs, as well as boost plants' defence, by enhancing their repellent, irritation and antifeedant properties against slugs. Prior studies in the context of other pests such as mites, coleopteran, mosquitoes and cockroaches show that essential oil-treated plants are able to demonstrate repellent, irritation and antifeedant effects towards these pest organisms [109,133,134]. Thus, essential oils might be able to offer all-round plant protection from slugs, which cannot be achieved using natural enemies.…”
Section: Natural Products As Bio-rational Control Agents Of Slugsmentioning
confidence: 99%
“…were used for studying the survival and thrashing of the three nematode species. The reason behind selection of above-mentioned oils is that most of the oils have been tested for molluscicidal, insecticidal and acaricidal activity in other studies (Mc Donnell et al 2016;Rios et al 2017;Barua et al 2017;Klein et al 2020). All the oils were procured from https ://www.essen tialo il.com except Birch Tar, which was ordered from https ://www.pipin grock .com/essen tial-oils-mc.…”
Section: Source Of Nematodes and Eosmentioning
confidence: 99%
“…EOs are plant-derived products, lipophilic in nature and possess the capacity to hinder metabolic, biochemical, physiological and behavioural functions of insects (Brattsten 1983;Tripathi et al 2009;Mossa 2016). Research findings show that different constituents of EOs, such as terpenes, alcohols, aldehydes, ethers, ketones, phenols and oxides (Boire et al 2013), are effective against various pests including insects, mites, fungi, slugs, snails and nematodes (Isman 2000;Mc Donnell et al 2016;Barua et al 2017;Klein et al 2020). In animal phyla, Nematoda is the second most diverse phylum after arthropods living in a wide range of habitats.…”
Section: Introductionmentioning
confidence: 99%